Intention to attend the Rainforest World Music Festival: Local visitor perspectives - Ting, H. (Cognizant Communication Corporation, 2017)
The annual Rainforest World Music Festival in Sarawak, Malaysia is a much celebrated tourism event and has global awareness as a festival of world music. Notwithstanding the popularity of the festival, there has been no study of visitor intentions. Drawing upon the theory of planned behavior, this study aims to determine the effect of attitude, subjective norm, perceived behavioral control, and past experience on behavioral intentions to attend the festival from the local visitor perspective. A questionnaire-based survey was administered using purposive sampling and ultimately 241 respondents participated. Multiple regressions analysis and t test were used to perform tests of relationship and difference. The findings show that although all the factors that are of interest have positive effects on intentions to visit the Festival, local visitors who have and have not attended previously exhibit very different behaviors. The study provides insights for the benefit of festival organizers and relevant stakeholders within the wider context of music festivals. © 2017 Cognizant, LLC.